(untitled) (Nigerian Journal of Technology, 2002)
Rainfall records are required for planning and development of water resources projects. Long term averages of rainfall are often needed. Decisions often have to be made with short term records, as long term rainfall records are not available for most parts of Nigeria. This study describes variations in some statistical measures as compared with their long term values. Records of 25 years will give estimates of mean rainfall within 4% of their long term values.